ImplementationOf Dispute Resolutionin the Field Copyright Upon Signing of the Beijing Treaty - Tohres, Steven Stanley; Heriyanti, Heriyanti; Pakpahan, Kartina (IJBLE Scientific Publications Community Inc., 2024)
Indonesia became a WIPO member country on December 18 2012 co-signed the Beijing Treaty at the World Intellectual General Assembly forum Property Organization in Geneva Switzerland. Implementation of the Beijing Treaty in Indonesia itself is quite interesting to study because the creative industry is in the form of performances Audiovisual in Indonesia itself is a profession so it is needed protection of copyright in the form of moral and economic rights to works audiovisuals, especially those broadcast or shown through media facilities technology. The legal research method used in this research is research normative juridical which is research conducted or aimed only at written regulations with the nature of descriptive analysis research which is a method that functions to describe or provide an overview of the object under study. The data source used is secondary data with analysis quantitative data. The government is expected to make clear policies regarding protection and classification and definition of AudioVisual Works in Indonesia because with Current technological developments make AudioVisual Works increasingly popular developing so that now a clear policy regarding protection is needed AudioVisual work that is in accordance with technological developments, Background The Beijing Treaty itself is linked to several conventions such as the Rome Convention so that the WPPT should be a basis for the government to create policies in the form of statutory regulations to protect works AudioVisual broadcast via electronic media or digital media and The current problems of creative industry players, especially in the field of work AudioVisual regarding the protection and recognition of AudioVisual's works aired through electronic media regarding this matter, it is hoped that the government will which has ratified the Beijing Treaty to create implementing regulations related to registration or recognition mechanisms and claims to the rights of perpetrators The creative industry is specifically related to performers of AudioVisual Works